A Wound Environment Control System to Avoid Major Amputation in Diabetic Foot Ulcers - Julien Vouillarmet; Gisele Fribourg; Lauriane Labaisse; Nellie Della-schiava (Medicina, 2023)
We report the case of a 58-year-old patient with a diabetic foot lesion at high risk of major amputation successfully treated by a new innovative wound environment control system.